Analisis Penggunaan Hiponim dan Hipernim dalam Koran Riau Pos Edisi Agustus 2020 - Ameliyatun Hidayah, Suci; Nazirun, Nazirun (UIR Press, 2024)
This research was motivated by hyponyms and hypernyms contained in the Riau Post Newspaper. A hyponym is a relation of meaning whose meaning is more solemn or whose meaning is considered part of another expression while a hypernym is a relation of meaning whose meaning is more general or whose meaning represents another expression. Formulate the problem in this study, namely, (1) how is the use of hyponyms in Riau Pos newspaper? (2) how is the use of hypernyms in Riau Pos newspaper? This study aims to (1) describe, analyze and interpret the use of hyponyms in Riau Pos newspaper (2) describe, analyze and interpret the use of hypernyms in Riau Pos newspaper. This type of research is qualitative research with content analysis methods. The theory used in semantic research from the books Chaer (2009), Djajasudarma (2012) and Tarigan (2009). The research approach is qualitative type library. The method used content analysis. The results of research from the analysis of the use of hyponyms and hypernyms in the Riau Pos newspaper are hyponyms there are 20 data, one of the data citations in which there is hyponymous data is